IL-33: A Potential Therapeutic Target in Autoimmune Diseases. (1st December 2012) - Wang, Song; Ding, Lei; Liu, Shan-Shan; Wang, Chao; Leng, Rui-Xue; Chen, Gui-Mei; Fan, Yin-Guang; Pan, Hai-Feng; Ye, Dong-Qing
Abstract : Interleukin 33 (IL-33) is a newly described member of the IL-1 superfamily of cytokines. Through activation of the ST2 receptor, which is widely expressed particularly by helper T 2 cells and mast cells, IL-33 is involved in T-cell–mediated immune responses. Many previous studies have demonstrated that IL-33 may have a pleiotropic function in different diseases, and it could represent a novel target for the treatment of a range of diseases. Recent works have explored the role of IL-33 in chronic autoimmune diseases, such as systemic sclerosis, inflammatory bowel disease, rheumatoid arthritis, and systemic lupus erythematosus. These results indicate that IL-33 may contribute to the pathogenesis of chronic autoimmune diseases. Hence, in this review, we discuss the biological features of IL-33 and summarize recent advances on the role of IL-33 in the pathogenesis and treatment of autoimmune diseases.